Initial development of wheat (Triticum aestivum) using phytohormone, zinc and inoculant seed treatment - Georgin, Jordana; Lazzari, Laudison; Lamego, Fabiane Pinto; Camponogara, Alexandre (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
We checked the effects on early development of wheat plants on the application of plant hormones (citicinina, gibberellin and auxin), inoculants (Azospirillum brasilense) and micronutrients (zinc) with the seed treatment, individually or associations between products. Two experiments were conducted: the first was held the germination test, noting the percentage of normal and abnormal seedlings, dead seeds and hard, and the length of the radicle, shoot and seedling length, the second experiment was carried out in a greenhouse using commercial substrate in plastic pots, observing the speed index of emergency, the shoot dry mass, dry mass of shoots and total dry mass of wheat plants 28 days after sowing. There was no significant difference between treatments for the variables related to germination. The treatments that were used with zinc showed better seedling length. All treatments behaved better than the witness to the accumulation of dry matter of shoot, except for the individual use of zinc, which behaved in an intermediate form. For the total dry mass all treatments proved better than the control, with emphasis on the uses of that fitihormônios presented with further development.